When dealing with a trinomial of the form:
![x^2+bx+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/6mrn15hyij6p7pm0mh1tfi1inr92v22kxn.png)
Compare the expression to that of a perfect square trinomial:
![(x+a)^2=x^2+2ax+a^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/eea9ekuwxh56h7u1b1fy8euvjkof1ed9ma.png)
We want 2a=b, so we can add a^2 - a^2 to be able to write the trinomial as a squared binomial plus a constant. Since a=b/2, we should add b^2/4 - b^2/4.
C)
![2x^2+2y^2+3x-5y=2](https://img.qammunity.org/2023/formulas/mathematics/high-school/dtzw9hz6odyf6wxcb2wmf5mybwunjfzp3v.png)
First, notice that the coefficient of x^2 and y^2 is not 1. We need it to be equal to 1 in order to use the former procedure. Divide both sides by 2:
![\begin{gathered} \Rightarrow(2x^2+2y^2+3x-5y)/(2)=(2)/(2) \\ \Rightarrow x^2+y^2+(3)/(2)x-(5)/(2)y=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4zvx5b5zbix0imqn3vxk3q63y2jbeyilk2.png)
The coefficient of x is 3/2, and comparing to the formula of the perfect square trinomial, then:
![\begin{gathered} 2a=(3)/(2) \\ \Rightarrow a=(3)/(4) \\ \Rightarrow a^2=(9)/(16) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/k2y5z6jgtek0edyvasb13rcptmoe6vhmwy.png)
Te coefficient of y is -5/2, and comparing to the formula of the perfect square trinomial, the constant term inside the binomial should be -5/4, so we need a constant term of 25/15 to complete the square. Add 9/16 and 25/16 to both sides of the equation:
![\Rightarrow x^2+y^2+(3)/(2)x-(5)/(2)y+(9)/(16)+(25)/(16)=1+(9)/(16)+(25)/(16)](https://img.qammunity.org/2023/formulas/mathematics/college/3hwk2foxo5pg4tqdhr5809jpoeb11rvelf.png)
Reorder the terms on the left hand side of the equation, and simplify the expression on the right hand side:
![\begin{gathered} \Rightarrow x^2+(3)/(2)x+(9)/(16)+y^2-(5)/(2)y+(25)/(16)=(25)/(8) \\ \Rightarrow(x+(3)/(4))^2+(y-(5)/(4))^2=(25)/(8) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/r8b7wzhvlslxaw44j2y0rb0czdue19xmqz.png)
The coordinates of the center of this circle, are:
![(-(3)/(4),(5)/(4))](https://img.qammunity.org/2023/formulas/mathematics/college/wstkf7np8bf52pszquk13svu0caoxa5tfp.png)
The radius is given by the square root of the constant term on the right hand side of the equation:
![\begin{gathered} r=\frac{\sqrt[]{25}}{8} \\ \Rightarrow r=(5)/(4)\sqrt[]{2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/matz54b146hzjr3dv6ihdt6a45nfdpltlm.png)
D)
![x^2+y^2-2x-8y=8](https://img.qammunity.org/2023/formulas/mathematics/college/sb4erxoa1wo2enorx0m9yvcckkam6evsbb.png)
The coefficient of x is -2, which should be twice the constant term inside the squared binomial. So, that constant term is -1, and (-1)^2=1. Add 1 to both sides and rewrite the polynomial on x as a squared binomial:
![\begin{gathered} \Rightarrow x^2+y^2-2x-8y+1=8+1 \\ \Rightarrow x^2-2x+1+y^2-8y=9 \\ \Rightarrow(x-1)^2+y^2-8y=9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8j3t25e49lbxvre4egokbbexrjz3lr7ayx.png)
The coefficient of y is -8, which should be twice the constant term inside the squared binomial. So, the constant term is -4, and (-4)^2=16. Add 16 to both sides and rewrite the polynomial on y as a squared binomial:
![\begin{gathered} \Rightarrow(x-1)^2+y^2-8y+16=9+16 \\ \Rightarrow(x-1)^2+(y-4)^2=25 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/aegjvvj8gsapx59iyqs9adwi1vsazpdi20.png)
The coordinates of the center of this circumference are (1,4), and the radius is equal to 5.